2022
DOI: 10.1186/s13075-022-02746-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting patient satisfaction related to cost and treatment effectiveness in rheumatoid arthritis: results from the multicenter observational cohort study, FRANK Registry

Abstract: Background To further improve rheumatoid arthritis (RA) treatment, it is necessary to understand each RA patient’s satisfaction and to identify the factors affecting their satisfaction. Despite the rise in medical costs for RA, little is known about the factors that influence patient satisfaction with the cost of treatment in RA patients. Methods This is a multicenter observational study of Japanese RA patients from the FRANK Registry with data ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
1
0
2
Order By: Relevance
“…This result can be explained by the high costs of bDMARDs [ 16 ]. Indeed, a study carried out in Japan showed that the use of biological treatment was a predictive factor of dissatisfaction (OR = 2.21, p < 0.001) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result can be explained by the high costs of bDMARDs [ 16 ]. Indeed, a study carried out in Japan showed that the use of biological treatment was a predictive factor of dissatisfaction (OR = 2.21, p < 0.001) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Через 12 месяцев на фоне коррекции терапевтической схемы число удовлетворенных лечением пациентов достигло 85%, причем большинство из них составляли лица, исходно довольные назначенной терапией -отношение шансов (ОШ) -2,98 (95% ДИ: 2,58-3,44) [16]. Японский регистр FRANK, включавший данные 2235 пациентов с РА, показал значения «очень высокую удовлетворенность» и «удовлетворенность» (шкала 1-6) в отношении повседневной активности у 58%, проводимым лечением -у 72%, общим результатом терапии -у 66% респондентов [17]. Согласно недавно проведенному анонимному телефонному и интернет-опросу 882 больных РА в Испании, 56,8% опрошенных считали, что у них сохраняется высокая активность болезни, 31,5% отметили «эмоциональное неблагополучие», а 17,3% сообщили, что не удовлетворены проводимым лечением [18].…”
Section: расхождение в оценках пациента и врачаunclassified
“…Возможность достижения данного результата показывает, например, исследование T. Fujiwara и соавт. [9], которые наблюдали японскую когорту FRANK, включавшую 2235 пациентов с РА (2017-2020 гг.). На фоне активной терапии (72% больных получали МТ; 31% -ГИБП или тсБПВП; 40% -глюкокортикоиды) ремиссия или НВА по DAS28 были достигнуты в 81% случаев.…”
Section: патогенетическая терапия ра и качество жизниunclassified